Carbon dioxide sequestration: influence of porous media on hydrate formation kinetics - Bhattacharjee, Gaurav; Kumar, Asheesh; Sakpal, Tushar; Kumar, Rajnish (ACS Sustainable Chemistry & Engineering, 2015)
In the present study, CO, sequestration by hydrate formation in porous sediments has been discussed. Two siliceous materials with high porosities, pumice and fire hardened red clay (FHRC), have been used as packing materials in a fixed bed setup to study hydrate formation kinetics. The results obtained using the aforementioned materials were compared with those obtained using silica sand and quartz. Carbon dioxide hydrate formation kinetics was studied at 3.0 MPa pressure and 274 K temperature. Two different types of experiments were conducted: (a) using a constant volume of water and (b) maintaining a constant bed height. These experiments were conducted using the different porous media individually as packing materials. It was observed that pumice as the porous medium showed better hydrate formation kinetics resulting in 46 mol % water to hydrate conversion in 5 h. Moreover, kinetics was enhanced with decrease in the bed height of pumice; this suggests that at field scale adaptation of CO, sequestration in geological formations, mass transfer limitations would be significant. The effects of particle size on hydrate formation kinetics were also investigated. It was observed that hydrate formation kinetics was enhanced with decrease in the particle size fraction.
Keywords: Bed height; Gas hydrate; gas uptake; Geological sequestration; Particle size